Thread rolling and performance evaluations of a new anti-loosening double thread bolt combining a single thread and multiple threads. (2017) - Shinbutsu, Toshinaka; Amano, Shuichi; Takemasu, Teruie; Kuwabara, Toshihiko; Shimura, Jyo
Abstract: We have devised new bolt fasteners based on an innovative double thread mechanism composed of a coarse single thread and coarse multiple threads (called DTB-II). In order to improve the rolling formability and the strength, the screw-thread of the DTB-II was fundamentally modified in this study. The number of multiple threads was reduced by one from the 3thread DTB-II (called 3-1thread DTB-II). The FEM thread rolling simulations were first performed using dedicated dies having a groove that followed the same outline as the thread profile of the modified DTB-II. The 3-1thread DTB-II was rolled precisely and the thread heights completely reached the target level at any cross-section, and the difference in the rolled filling rate remarkably decreased due to the material flow in the circumferential direction. The equivalent plastic strain was intensively high at the groove bottom where a coarse single thread was traversed by bottom of multiple threads, that might cause some surface defects. The actual forming states in the thread rolling experiments well reproduced the FE-simulation results. The performance evaluation tests show that the 3-1thread DTB-II with the double nut structure has a practically sufficient tensile strength and its anti-loosening performance clearly exceeds that of the conventional DTB-I composed of a coarse-single thread and a fine-single thread.